Evaluation of environmental attitudes of a sample of Brazilian undergraduate students (Research, Society and Development, 2019)
Environmental attitudes are important once they predict environmental behavior and its promotion could help to achieve sustainability. We aimed to evaluate the environmental attitudes of 196 students enrolled in undergraduate courses: biology, chemistry, Portuguese language, and pedagogy, from a Brazilian university. Data were analyzed with three- and four-way analysis of variance (ANOVA). We found that biology students are those that present more pro-environmental attitudes while chemistry students are those with lower pro-environmental attitudes. Gender can also be a factor influencing attitudes, with female and male students differently depending on the course. School year influence also depends on the course. The subjects related to the environment in the curriculum influence student’s attitudes. Thus, we suggest that they should be addressed also to other study areas.